Down-regulation of lncRNA XIST inhibits cell proliferation via regulating miR-744/RING1 axis in non-small cell lung cancer. (18th July 2019) - Wang, Jinglu; Cai, Haibo; Dai, Zhaoxia; Wang, Gang
Abstract : Long non-coding RNAs (lncRNAs) are known to be potential factors in promoting tumor progression. However, the function and mechanism of lncRNA XIST in non-small cell lung cancer (NSCLC) remains poorly understood. The expression levels of lncRNA XIST in NSCLC tissues and cell lines were detected with real-time PCR, and the correlation of the expression level of XIST with histopathological characteristics and prognosis was analyzed. The biological function of lncRNA XIST was validated through assays in vivo and in vitro . The expression of lncRNA XIST was significantly up-regulated in NSCLC tissues. In addition, overexpression of XIST was positively correlated with the advanced clinical status of tumors, as well as poor overall survival and DFS. A tumor suppressive effect was presented via functional knockdown of lncRNA XIST. Up-regulation of XIST enhanced the proliferation, migration, and invasion ability of NSCLC cells both in vivo and in vitro . Mechanically, it was indicated that XIST could serve as an endogenous competitive RNA modulating miR-744, leading to the miR-744/RING1 signaling pathway inhibition and Wnt/β-catenin signaling pathway activation. Taken together, it was confirmed here that XIST overexpression is associated with tumor progression phenotype and the newly discovered XIST/miR-744/RING1 axis, which could serve as a potential biomarker and therapeutic target for NSCLC.